1999
DOI: 10.1345/aph.18296
|View full text |Cite
|
Sign up to set email alerts
|

Dextromethorphan and Diabetic Neuropathy

Abstract: There are insufficient safety and efficacy data to justify the use of dextromethorphan for treating painful diabetic neuropathy. Further clinical trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…Up to 450 bed-days were therefore saved as a result of domiciliary initiation. Overall concordance rate was 84.1% (n = 111) with little difference in dropout rate between home and hospital initiation (17.3% (n = 12) vs 14.2% (n = 9)), similar to existing data for the outpatient department (82% concordance)1 and hospital initiation (75% and 97% concordance) 2 3. Patients with chronic obstructive pulmonary disease were least likely to tolerate domiciliary initiation.…”
Section: P12 Retrospective Evaluation Of Home Initiation For Long-tersupporting
confidence: 67%
“…Up to 450 bed-days were therefore saved as a result of domiciliary initiation. Overall concordance rate was 84.1% (n = 111) with little difference in dropout rate between home and hospital initiation (17.3% (n = 12) vs 14.2% (n = 9)), similar to existing data for the outpatient department (82% concordance)1 and hospital initiation (75% and 97% concordance) 2 3. Patients with chronic obstructive pulmonary disease were least likely to tolerate domiciliary initiation.…”
Section: P12 Retrospective Evaluation Of Home Initiation For Long-tersupporting
confidence: 67%
“…The stimulation of NMDA receptors can result in the stimulation of the second-order neurons in the spinal cord leading to an influx of calcium. Two studies have analyzed the effectiveness of dextromethorphan in diabetic painful neuropathy and postherpetic neuralgia [73,74]. Both studies showed the dextromethorphan reduced the pain intensity in diabetic painful neuropathy but not in postherpetic neuralgia.…”
Section: Dextromethorphanmentioning
confidence: 99%
“…The available efficacy and safety data collected in these settings are insufficient, and further clinical trials are needed. Because dextromethorphan is an NMDA receptor antagonist, it has been investigated for its analgesic properties and found useful for diabetic neuropathy [19,67]. High doses were required (mean 300 mg/day).…”
Section: Dextromethorphanmentioning
confidence: 99%